2019
DOI: 10.33564/ijeast.2019.v04i05.076
|View full text |Cite
|
Sign up to set email alerts
|

Movie Recommendation System Using Bag of Words and Scikit-Learn

Abstract: Recommendation systems play an important role in our everyday life. Starting from movie/music streaming sites like Netflix or Spotify to the most basic search engines, the core component is comprised of recommendation systems. Even the technology giant Google is known for its search engine above everything else. To emphasize its importance we aim to build a simple recommendation system using the IMDB movie database. Our finished web application can suggest similar movies based on the input provided by the user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this research, a deep learning model for recommendation systems is proposed by integrating Convolutional Neural Network and Matrix Factorization to add extra information and extract contexts before training, attempting to enhance recommendation accuracy and context understanding. Despite substantial previous efforts [21,63,64], this study adds additional information on both user and item description documents and applied Convolutional Neural Networks to efficiently capture their local features. Furthermore, this research adds bias to the observed ratings to avoid overfitting issues and uses Matrix Factorization to create relationships between users and items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, a deep learning model for recommendation systems is proposed by integrating Convolutional Neural Network and Matrix Factorization to add extra information and extract contexts before training, attempting to enhance recommendation accuracy and context understanding. Despite substantial previous efforts [21,63,64], this study adds additional information on both user and item description documents and applied Convolutional Neural Networks to efficiently capture their local features. Furthermore, this research adds bias to the observed ratings to avoid overfitting issues and uses Matrix Factorization to create relationships between users and items.…”
Section: Discussionmentioning
confidence: 99%
“…In order to address the above data sparseness limitation, in this paper, different factors have been added to the recommendation system such as user information, user interactions, and product description documents instead of only using review data, attempting to enhance the accuracy of the system. Moreover, traditional information retrieval methods mostly use the bag-of-words model, which ignores the context information of the text document [21].…”
Section: Introductionmentioning
confidence: 99%